(untitled) (CIPEEX, 2026)
Introduction: The ability to rise from a seated position is a prerequisite for the functional independence of the elderly. Although the activity of getting up and sitting down represents a natural and complex functional movement, the strength of the lower limbs is also an important predictor of performance in this activity. Objective: To assess the functional capacity of elderly individuals using the sit-to-stand test. Method: A cross-sectional study with probabilistic sampling, in which 213 elderly people registered at the Basic Health Unit (UBS) Vila São José in Gurupi/TO were evaluated, performing the sit-to-stand physical test for 1 minute.Results: In the Sit and Stand test, two groups of elderly people were identified, Group 1, consisting of 147 elderly individuals (69%), showed low lower limb muscle strength conditioning, while Group 2, made up of 66 elderly individuals (31%), showed normal conditioning. Conclusion: The study revealed a high prevalence of low strength conditioning in the lower limbs among the elderly individuals evaluated at UBS Vila São José, highlighting the importance of continuous monitoring of functional capacity, especially through the Sit and Stand test.